2016
DOI: 10.1038/srep30337
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tlx3 by Pax6 is required for the restricted expression of Chrnα3 in Cerebellar Granule Neuron progenitors during development

Abstract: Homeobox gene Tlx3 is known to promote glutamatergic differentiation and is expressed in post-mitotic neurons of CNS. Contrary to this here, we discovered that Tlx3 is expressed in the proliferating progenitors of the external granule layer in the cerebellum, and examined factors that regulate this expression. Using Pax6−/−Sey mouse model and molecular interaction studies we demonstrate Pax6 is a key activator of Tlx3 specifically in cerebellum, and induces its expression starting at embryonic day (E)15. By Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The region upstream of Solute carrier family 11 member 1 ( SLC11A1 ), a gene expected to be active in the spleen and encodes a membrane protein involved with macrophage development, displayed sequence pileup for active marks H3K4me3 and H3K27ac and low levels of DNA methylation directly upstream ( Figure 3B ) ( Hedges et al, 2013 ). Paired box 6 ( PAX6 ) is known to be involved in the development of neural tissues and maturation of granule neurons in the cerebellum and is known to have a promoter and multiple enhancers both upstream and downstream of the gene ( Ha et al, 2015 ; Divya et al, 2016 ). Furthermore, PAX6 has greater expression in the cerebellum than other tissues in sheep which is supported by the sequence pileup of active histone marks H3K4me3 and H3K27ac, with some activity of H3K4me1 and little DNA methylation ( Figure 3C ) ( Jiang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The region upstream of Solute carrier family 11 member 1 ( SLC11A1 ), a gene expected to be active in the spleen and encodes a membrane protein involved with macrophage development, displayed sequence pileup for active marks H3K4me3 and H3K27ac and low levels of DNA methylation directly upstream ( Figure 3B ) ( Hedges et al, 2013 ). Paired box 6 ( PAX6 ) is known to be involved in the development of neural tissues and maturation of granule neurons in the cerebellum and is known to have a promoter and multiple enhancers both upstream and downstream of the gene ( Ha et al, 2015 ; Divya et al, 2016 ). Furthermore, PAX6 has greater expression in the cerebellum than other tissues in sheep which is supported by the sequence pileup of active histone marks H3K4me3 and H3K27ac, with some activity of H3K4me1 and little DNA methylation ( Figure 3C ) ( Jiang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…PGV Basic vector is a promoter less luciferase vector procured from Promega. pCAGIG-Pax6 41 was used to over-express Pax6, and Pax6 was down-regulated using different siRNA oligos cloned into the iLenti-siRNA-GFP vector using specifically designed oligos (Table S4 ) according to manufacturer’s protocol (Applied Biological Materials, Inc). siRNA oligo insertion into iLenti-siRNA-GFP vector was further confirmed by sequencing using ABI sequencing protocol.…”
Section: Methodsmentioning
confidence: 99%
“…A similar restriction associated with the PZ/NZ transverse boundary ( Figure 7A ) is seen for the HOX homeodomain transcription factor gene Tlx3 (Logan et al, 2002 ), shown to have a selector role in glutamatergic subtype specification (Shimomura et al, 2015 ). Tlx3 , a gene whose expression is induced by PAX6, is expressed in a highly restricted manner in the iEGL and oEGL plus mature cerebellar granule neurons of the posterior cerebellar lobes, where it is required for the localized expression of the nicotinic cholinergic receptor-α3 subunit (CHRN-α3) and other factors involved in neuronal migration and connectivity (Divya et al, 2016 ). Other transverse boundaries are seen in birth dating studies.…”
Section: Granule Cell Birth In the Eglmentioning
confidence: 99%